2008
DOI: 10.2341/07-89
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Two In-office Whitening Agents on the Enamel Surface In Vivo: A Morphological and Non-contact Profilometric Study

Abstract: This study evaluated the morphological effects produced in vivo by two in-office bleaching agents on enamel surface roughness using a noncontact profilometric analysis of epoxy replicas. The null hypothesis tested was that there would be no difference in the micromorphology of the enamel surface during or after bleaching with two different bleaching agents. Eighteen subjects were selected and randomly assigned to two treatment groups (n=9). The tooth whitening materials tested were 38% hydrogen peroxide (HP) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
1
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 32 publications
2
52
1
10
Order By: Relevance
“…21,22 It appears that these small changes in the enamel produced by bleaching did not seem to be a problem as they were resolved by the remineralizing action of saliva. 23 This explains why previous application of fluoride before bleaching was not capable of reducing the bleaching-induced tooth sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 It appears that these small changes in the enamel produced by bleaching did not seem to be a problem as they were resolved by the remineralizing action of saliva. 23 This explains why previous application of fluoride before bleaching was not capable of reducing the bleaching-induced tooth sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…A high concentration of hydrogen peroxide (G 4 ; pH = 7.01) caused a generalized dissolution of nonprismatic enamel, [5,14,16,17] however, without exposing enamel prisms [ Figures 10-12]. The quick dissolution and slow recrystallization of non-prismatic enamel resulted in a surface showing some erosions.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have evaluated the effects of peroxide-containing products on the physical and chemical properties of tooth. However, researches in this area have been controversial [6][7][8][9][10] . Pobbe et al 18 evaluated the fracture resistance of endodontically treated teeth submitted to dental bleaching.…”
Section: Discussionmentioning
confidence: 99%
“…The use of these traditional bleaching materials, especially hydrogen peroxide, has been associated with complications such as cervical root reabsorption, increased dentine permeability, changes in the biomechanical properties of tooth related to alteration in the chemical structure of tooth occurred by demineralization and quantitative mineral loss 6,7 . However, some studies reported that there was no evident change in mechanical and morphology after bleaching treatment 3,[8][9][10] . In addition, the endodontically treated teeth have high risk of biomechanical failure caused by elasticity of dentin decreased, lost of tooth structure from previous caries, pre-existing restorations, coronary access for endododontic treatment, suggesting the need for additional restorative considerations [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%